Citizen Science in A Small World of Singlish Words - SIEW, Cynthia S. Q. (Institutional Knowledge at Singapore Management University, 2024)
Lightning talk “Citizen Science in A Small World of Singlish Words: A Word Association Study” by Winner of the Singapore Open Research Awards 2024, Assistant Professor Cynthia S. Q. SIEW from National University of Singapore. Abstract: Motivated by the lack of representation of non-dominant English dialects in existing psycholinguistic word norms, our project aims to create a database of semantic, affective, and word association norms for Singapore English words. Our research lab prioritises making all of our collected datasets and analysis scripts openly available through online repositories, such as Open Science Framework (OSF), ensuring reproducibility and reusability of research findings. This approach facilitates the creation of culturally relevant AI and computational models for linguistic analysis of Singaporean text. By embracing open science practices and promoting citizen science initiatives, our work contributes significantly to advancing cross-cultural psycholinguistic research and promoting open science principles within the social sciences. Website: https://libguides.ntu.edu.sg/SGopenresearchawards/Siew